Changes in ferroelectric properties of ceramics in lead magnesium niobate-lead titanate system with compressive stress - Muangjai Unruan (2018)
Effects of compressive stress on the ferroelectric properties of Pb (Mg1/3 Nb2/3) O3 - PbTiO3 (PMN-PT) ceramics were investigated. The ceramics with the formula (1-x) Pb (Mg1/3 Nb2/3) O3 - (x) PbTiO3 or (1-x) PMN- (x) PT (x=0.1-0.5) were prepared by a conventional mixed-oxide method. Dense perovskite-phase PMN-PT ceramics with a uniform microstructure were obtained. The ferroelectric properties were measured under compressive stress (0-75 MPa) using a homebuilt compressometer in conjunction with a modified Sawyer-Tower circuit. The experimental results revealed that the superimposed compression stress significantly reduced both the dissipation energy and the polarizations of the near morphotropic phase boundary compositions, i.e., 0.8PMN-0.2PT, 0.7PMN-0.3PT, and 0.6PMN-0.4PT, while the stress influence was much less in other compositions. On the contrary, the applied compressive stress showed little or no influence on the coercive field. These results were interpreted through the non- 180°ferroelastic domain switching processes and the stress induced decrease in the switchable part of domains. © 2008 American Institute of Physics.